Audit Kualitas Perangkat Lunak pada Sistem Informasi Inventori Berbasis Web: Studi Kasus Repositori Open Source Menggunakan Standar ISO/IEC 29119 - Resnawati Kusnandar; Muhamad Yusup; Chairul Anwar (Journal of Information Systems and Business Technology, 2025)
The reuse of open-source code from public repositories like GitHub to accelerate business information system development often neglects quality assurance aspects. This practice poses high risks as raw code may contain hidden defects that jeopardize data integrity. This study aims to conduct an independent quality audit on the "Shoe Store Inventory System" based on Native PHP and MySQL acquired from the depthgilang GitHub repository. The testing framework adopts the international standard ISO/IEC 29119 to ensure a systematic, standardized, and objective verification and validation process. The research methodology employs Dynamic Testing with a Black Box approach and Equivalence Partitioning technique. Testing focused on validating CRUD (Create, Read, Update, Delete) functionalities, system stability, and basic data input security. Based on the execution of 28 test cases, this research revealed empirical facts regarding low code quality. Although the user interface functions correctly, the system experienced a fatal Critical Failure in the form of database connection loss ("MySQL server has gone away") during data storage operations. Furthermore, Major category security loopholes were discovered, specifically SQL Injection and Stored Cross-Site Scripting (XSS) vulnerabilities due to the absence of input sanitation, as well as business logic errors allowing negative stock values. In conclusion, this software is declared as not meeting industrial eligibility standards for production release. The code requires deep structural refactoring on database connection management and security protocols before being safe for operational utilization.